Triggering Receptors Expressed on Myeloid Cells 2 Promotes Corneal Resistance Against Pseudomonas aeruginosa by Inhibiting Caspase-1-Dependent Pyroptosis - Qu, Wenting; Wang, Yi; Wu, Yongjian; Liu, Yiting; Chen, Kang; Liu, Xi; Zou, Zhengyu; Huang, Xi; Wu, Minhao (Frontiers in Immunology, 2018)
Triggering receptors expressed on myeloid cells 2 (TREM2) is a novel cell surface receptor and functions as an immunomodulatory receptor in infectious diseases. In this study, we investigated the function and regulatory mechanism of TREM2 in Pseudomonas aeruginosa (P. aeruginosa) keratitis. We found that P. aeruginosa keratitis was more severe in Trem2-/- vs wildtype C57BL/6 mice as indicated by the increased clinical scores, bacterial load and cornea pathology. The exacerbated disease progression caused by TREM2 deficiency was associated with boosted activation of caspase-1 and subsequent pyroptosis as well as increased expression of IL-1β and IL-18. In addition, blockage of pyroptosis by caspase-1 inhibitor not only recovered the severe cornea pathology developed in Trem2-/- mice, but also restored the P. aeruginosa clearance suppressed by TREM2 deficiency. Our study demonstrated that TREM2 promotes host resistance against P. aeruginosa keratitis by inhibiting caspase-1-dependent pyroptosis, which provides new insights of TREM2-mediated anti-bacterial immunity.